HYPOTENSIVE THERAPY: DYNAMICS OF HEARING IN PATIENTS WITH ARTERIAL HYPERTENSION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Hypertension (AH) was designated by Russian scientists as the greatest non-infectious pandemic in the history of mankind [7-14]. This definition, given at the end of the 20th century, retains its significance at the beginning of the 21st century, when an increase in the upward trend in the incidence of GB was noted. Currently, in the fight against hypertension, it is important not only to reduce blood pressure, but also to prevent and treat organ complications [3,5]. As is known, among organ complications, cerebrovascular ones are life-threatening. In particular, damage to the auditory analyzer significantly reduces the quality of life of patients with GB. Therefore, it is very important to study the state of auditory function in patients with hypertension, to determine the relationship of this pathology in general with dyscirculatory disorders of the brain. This issue has not been covered enough in the literature, only a few reports [1-6] discuss certain aspects of this problem.